The Amulet of Samarkand - Stroud, Jonathan (Stroud, Jonathan. Bartimaeus trilogy, 2003)
Nathaniel, a magician's apprentice, summons up the djinni Bartimaeus and instructs him to steal the Amulet of Samarkand from the powerful magician Simon Lovelace.